AKR1B1-Induced Epithelial-Mesenchymal Transition Mediated by RAGE-Oxidative Stress in Diabetic Cataract Lens - Tsung-Tien Wu; Ying-Ying Chen; Hui-Yu Chang; Ya-Hsin Kung; Ching-Jiunn Tseng; Pei-Wen Cheng (MDPI AG, 2020)
Purpose: Cataracts are a major cause of visual acuity deterioration in diabetes mellitus (DM) in developed and developing countries. Studies have demonstrated that overproduction of AKR1B1 and receptor for advanced glycation end products (RAGE) plays a major role in the pathogenesis of diabetic cataracts, but it is unclear whether the prevalence of diabetic cataracts is related to epithelial−mesenchymal transition (EMT) in lens epithelial cells. This study aimed to analyze the role of EMT in cataract formation of DM patients. Methods: Immunofluorescence and immunohistochemistry assays were used to estimate AKR1B1, RAGE, AMPK, and EMT levels in epithelial human lens of DM or non-DM cataracts. Results: Immunohistochemical staining demonstrated that pathologic phases and N-cadherin expression levels were significantly higher in epithelial human lens of DM (+) compared to DM (−) cataracts. Immunofluorescent staining showed that AKR1B1 and RAGE were significantly higher in epithelial human lens of DM (+) compared to DM (−) cataracts. Interestingly, acetyl superoxide dismutase 2 (AcSOD2) levels were significantly higher in DM patients’ lens epithelial cells (LECs), whereas AMPKT172 phosphorylation was significantly increased in non-DM patients. This indicates that AMPKT172 might be related to superoxide reduction and diabetic cataract formation. Conclusions: Our results suggest that AKR1B1 overexpression can decrease AMPK activation, thereby increasing AcSOD2 and RAGE-induced EMT in epithelial human lens of DM cataracts. These novel findings suggest that AKR inhibitors may be candidates for the pharmacological prevention of cataracts in patients with DM.